The Heroic Archetypes and the Reinvention of Aswang Character in Segundo Matias’ Moymoy Lulumboy Ang Batang Aswang - Illana, Mary Ann Alcantara (OKARA: Jurnal Bahasa dan Sastra, 2021)
Marginalized and queer heroes are being recognized in the resurgence of various types of characters in contemporary hero narratives. In challenging the normative conventions, there are heroic values in the ambiguous presentation of their character which are revived and valorized based on the heroic archetypes presented in the story. Given this, how do we reconcile the normative conventions of hero attributed to queer and deviant representation of his character and heroic deeds? This paper analyzes the contemporary work of Segundo Matias’ Moymoy Lulumboy: Ang Batang Aswang. Patterned from Joseph Campbell’s normative structure of hero’s journey, which models the representation of various nature of character heroes and their established heroic archetypes, this study revealed that a category of heroic deviant exists in portraying character hero in the revival of Aswang lore in contemporary urban legend. Furthermore, this paper affirms that the resurrection of the archetypal pattern and the marginal presentation of the hero and his journey present a re-inscripted image of Aswang from a "rigidly static" to a semi-heroic ascension.